Applying Authentic Assessment in Fiqh Learning at Madrasah Ibtidaiyah - Afriyanto Afriyanto; Hengki Saputra (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Learning evaluation practices still tend to rely on conventional assessments that focus primarily on cognitive aspects, thereby failing to comprehensively capture students’ learning achievements. Objective: This study aims to describe the implementation of authentic assessment in Fiqh lessons at Madrasah Ibtidaiyah and to analyse its impact on students’ conceptual understanding, learning engagement, and the application of Fiqh values. Method: This study employed a descriptive qualitative approach. Data were collected through classroom observations, in-depth interviews, and documentation analysis. Findings: The findings indicate that authentic assessment enhances students’ understanding of Fiqh concepts, promotes active participation in the learning process, and facilitates the application of Fiqh values in real-life contexts. Furthermore, authentic assessment enables teachers to holistically evaluate students’ development across cognitive, affective, and psychomotor domains. Conclusion: Authentic assessment is an effective and relevant evaluation strategy for Fiqh learning at Madrasah Ibtidaiyah, as it supports meaningful learning and comprehensive student assessment. Contribution: This study contributes empirical and practical insights into the implementation of authentic assessment as a contextual and holistic evaluation alternative in Islamic education, particularly at the elementary level.